2012
DOI: 10.2169/internalmedicine.51.6378
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Neuroendocrine Carcinoma of the Pancreas Responsive to Combination Therapy with Gemcitabine and S-1

Abstract: Poorly differentiated neuroendocrine carcinoma is a very rare malignancy, but it is characterized by agressive histological features and a poor clinical prognosis. We report a 42-year-old man who had poorly differentiated neuroendocrine carcinoma of the pancreas with multiple liver metastases. We administrated combined chemotherapy with S-1 and gemcitabine. This treatment was efficacious and well tolerated, and then this patient obtained objective partial response for 7 months and survived for 13 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[ 10 12 ] However, several case reports also showed that S-1 was effective for patients with high-grade endocrine neoplasms of the pancreas. [ 13 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 12 ] However, several case reports also showed that S-1 was effective for patients with high-grade endocrine neoplasms of the pancreas. [ 13 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we decided to administer chemotherapy with S-1 and octreotide. To the best of our knowledge, several patients with pancreatic NETs who were treated with S-1 have been reported in the Japanese and English literature (Table 1) [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. S-1 was used as a single agent, as well as in combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…S-1 consists of a combination of drugs such as octreotide, gemcitabine, and streptozocin. The anti-growth effect of S-1 containing chemotherapy varies from partial response to progressive disease by case reports [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for poorly-differentiated NECs of the pancreas, the NCCN guidelines and North American Neuroendocrine Tumor Society consensus guidelines (6) recommend combined chemotherapy with cisplatin and etoposide, one of the standard regimens employed for the treatment of small cell lung cancer. In addition, the efficacies of GEM and oral S-1 (7), bevacizumab (8), folinic acid, fluorouracil and irinotecan (9), valproic acid (10) and other treatments have also been reported.…”
Section: Discussionmentioning
confidence: 99%